Reanimacija poljske poezije - Cudak, Romuald (Jezik in slovstvo, 2017)
The sketch outlines contemporary tendencies in Polish poetry, which can be subsumed under global trends connecting poetry with certain features of modern culture: iconicity and secondary orality. The author identifies three forms of the visualisation and oralisation of a poetic text: extreme exploitation of material components of print (visual poetry), forsaking the written word for telewriting and image (cyber poetry, video poetry), and a melancholic attempt to return to the oral word as the substance of poetry (slam poetry, rap). The author views these tendencies as an attempt to revitalise poetry, which became fossilised in the form of "poetry for reading" and as such ceased reaching its audience.
Keywords: Polish literature; poljska književnost; poljska poezija; kibernetična poezija; videopoezija; slamerska poezija